Digital Book Student Development Course Based on Team-Based Learning in The Era of Society 5.0 - Desi Nurhikmahyanti; Hani’ Rosyidah; Rini Setiawati (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
The independent campus policy has yet to be prepared thoroughly and correctly as the system is still partial, making it difficult for universities to implement. The Student Development course needs a digital book that integrates the team-based learning model in the era of Society 5.0. This development research aims to create a digital book for student development courses based on Team-based learning in the era of Society 5.0. The stages in this development research are based on the Borg & Gall model. The research subjects were 1st-semester students taking student development courses. The data collection techniques used were tests and non-tests. Qualitative and quantitative analysis were used in the data analysis. This research and development resulted in the digital book used in the Student Development course based on Team-based learning in the era of Society 5.0 being included in the valid category with an average learning device validation score of 0.8. This research concludes that this learning tool is suitable for testing students during lectures. This research implies that digital book media, which integrates the team-based learning mode, can support the lecture process and provide students with skills.